The virtuous city of al-Farabi and Aurovil city in India - Iskakova, Z.E. (Journal of Oriental Studies, 2020)
This article is devoted to the theory of the virtuous city in the heritage of al-Farabi and its embodiment in Aurovil, India. The idea of a perfect society and a perfect city has been attractive for the best minds of mankind since the antiquity. Al-Farabi wrote a treatise on his vision of a virtuous city, in which he outlined his idea of “ideal society”. Many of its positions were reflected in the city of Aurovil, which was created as the City of the Future - a city free from any religious and political views and beliefs. Life in the city is based on the principles of justice and humanism, free labor and the happiness of each citizen. Research on this topic is being carried out for the first time in Kazakhstani oriental studies. It is based on a comparative historical method and has a preventive nature in order to stimulate further researches in this direction. The results of the study allow us to conclude that the ideas of humanism and philanthropy are timeless, giving us a hope for their mandatory implementation. The value of the heritage of al-Farabi is confirmed by time, which speaks of his genius and historical insight. Utopian, at first glance, ideas about an ideal society are being realized today, which allows us to look with hope into the future of humanity. Key words: Al-Farabi, virtuous city, ruler, happiness, city of the future, Aurovil, India.